Predictive role of absolute lymphocyte count in daratumumab-treated patients with relapsed/refractory multiple myeloma - Hee Jeong Cho; Jae-Cheol Jo; Yoo Jin Lee; Myung Won Lee; Do Young Kim; Ho Jin Shin; Sung Nam Im; Ji Hyun Lee; Sung Hwa Bae; Young Rok Do; Won Sik Lee; Min Kyung Kim; et al. (The Korean Journal of Internal Medicine, 2023)
Background/Aims Daratumumab has shown an encouraging antitumor effect in patients with multiple myeloma (MM), and was known to alter the immune properties by off-targeting immunosuppressive cells. Here, we aimed to evaluate the change in absolute lymphocyte count (ALC) as a surrogate marker for predicting survival outcomes of patients treated with daratumumab. Methods Between 2018 and 2021, the medical records of patients with relapsed/refractory MM (RRMM) treated with daratumumab monotherapy at 10 centers in South Korea were reviewed. We collected the ALC data at pre-infusion (D0), day 2 after the first infusion (D2), and prior to the third cycle of daratumumab therapy (D56). Results Fifty patients who were administered at least two cycles of daratumumab were included. Overall response rate was 54.0% after two cycles of daratumumab treatment. On D2, almost all patients experienced a marked reduction in ALC. However, an increase in ALC on D56 (ALCD56) was observed in patients with non-progressive disease, whereas failure of ALC recovery was noted in those with progressive disease. Patients with ALCD56 > 700/μL (n = 39, 78.0%) had prolonged progression-free survival (PFS) and overall survival (OS) than those with ALCD56 ≤ 700/μL (median PFS: 5.8 months vs. 2.6 months, p = 0.025; median OS: 24.1 months vs. 6.1 months, p = 0.004). In addition, ALCD56 >700/μL was a significant favorable prognostic factor for PFS (hazard ratio [HR], 0.22; p = 0.003) and OS (HR, 0.23; p = 0.012). Conclusions Increase in ALC during daratumumab treatment was significantly associated with prolonged survival outcomes in patients with RRMM. The ALC value can predict clinical outcomes in patients treated with daratumumab.